2016
DOI: 10.1021/acsami.6b03905
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Triggered Switchable Nanoparticles for Targeted Chemo/Photothermal Cancer Therapy

Abstract: Accumulation of nanoparticles in solid tumors depends on their extravasation, but their efficacy is often compromised by intrinsic physiological heterogeneity in tumors. The conventional solutions to circumvent this problem are size control of nanoparticles or increasing the vascular permeability. The aim of this study is to investigate the combination effect of size variation of stimuli-responsive nanoparticles and improved vascular permeability triggered by near-infrared (NIR) light irradiation. Doxorubicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 39 publications
2
49
0
Order By: Relevance
“…51 External stimuli, including variations in temperature, magnetic fields, 52,53 and NIR light, 54,55 have been well employed in drug delivery systems in previous studies. However, compared with the LDI in this study, externally placed magnets have no antitumor efficacy themselves, while NIR light or thermotherapy are not widely applied.…”
mentioning
confidence: 99%
“…51 External stimuli, including variations in temperature, magnetic fields, 52,53 and NIR light, 54,55 have been well employed in drug delivery systems in previous studies. However, compared with the LDI in this study, externally placed magnets have no antitumor efficacy themselves, while NIR light or thermotherapy are not widely applied.…”
mentioning
confidence: 99%
“…The pRGO@MS (DOX)-HA showed excellent photothermal properties and good dispersibility under NIR laser irradiation. Gao et al 62 developed a thermal/pH dual-sensitive nanocarrier for the treatment of bladder cancer. Their results revealed that chemo/photothermal targeted therapy might be more advantageous than conventional therapeutics for bladder cancer.…”
Section: Combined Cancer Therapymentioning
confidence: 99%
“…In the scope of this review, frames are (but not limited to) carbon-based nanomaterials (mesoporous carbon nanoparticle, graphene, graphene oxide, single- or multi-walled carbon nanotubes, etc.) [ 29 , 36 , 37 , 39 , 41 , 59 , 63 , 66 , 68 , 79 , 94 , 95 , 96 , 97 , 98 ], silica-based nanomaterials [ 30 , 31 , 93 , 99 ], nanogold materials [ 75 , 77 , 78 , 99 , 100 , 101 , 102 , 103 ], polydopamine (PDA) [ 28 , 47 , 67 ], polypyrrole (PPy) [ 27 , 49 , 69 , 70 , 71 , 72 , 73 , 94 ], metal organic frameworks [ 73 , 104 ], Prussian blue [ 104 , 115 ], other inorganic materials [ 22 , 35 , 69 , 105 ,…”
Section: The Basics Of Polymer-based Nanocarriersmentioning
confidence: 99%